Review of CLIMEX and MaxEnt for studying species distribution in South Korea - Byeon, Dae-hyeon; Jung, Sunghoon; Lee, Wang-Hee (Journal of Asia-Pacific biodiversity, 2018)
The use of species distribution modeling to predict the possible extent of suitable habitat for significant pests has been accepted as an efficient method for determining effective management and countermeasures. CLIMEX and MaxEnt are widely used software for creating species distribution models. CLIMEX predicts climatic suitability of a specific region for target species, whereas MaxEnt uses various environmental variables with presence-only data to assess potential distribution. The software has so far mainly been used for assessing large countries and continents but scarcely used to assess relatively small areas such as South Korea. The objective of this study was to review previous CLIMEX- and MaxEnt-based studies in South Korea and their effectiveness in predicting the distribution of species that could cause nation-wide damage. We expect that, by reviewing recently used species distribution models and their results, this study will provide the basic information necessary to predict potential species distribution.